Diversification of cropping systems to improve national food security - Sebastián Parra Londoño (Magna Scientia UCEVA, 2023)
The aim of this reflection is to study and promote the diversification of cropping systems as a strategy for the improvement of food security at national level. Food security is a global challenge that nations continue to address. Agricultural systems should address this issue; however, traditional practices may not be sufficient to produce enough food for the growing population. Conversely, intensive agriculture has significantly impacted the environment by increasing the use of fertilizers and freshwater, expanding cultivation lands, and reducing biodiversity. Therefore, innovative techniques are necessary to enhance agricultural productivity while respecting planetary environmental limits that are essential for the resilience of the earth. Enhancing cropping diversity in agricultural systems could significantly increase yield and food production, optimizing land usage efficiency. This brief analysis examines the diversity of crop species in Colombia from 2006 to 2022 and its impact on agricultural production. National crop diversity has increased over time, with higher heterogeneity observed in regions such as Cundinamarca, Boyacá Antioquia, Santander, Nariño, and Valle del Cauca. Additionally, significant correlations exist between the number of crops cultivated per location and agricultural production, emphasizing the significance of diversity in food systems. Increasing crop diversity can not only improve national food security but also aid in maintaining ecosystem integrity. Further research should focus on assessing the impact of various farming system diversification, approaches on yield stability and food security at the farm level